Fitness monitoring in elite soccer players: group vs. individual analyses - Rabbani, A.; Kargarfard, M.; Twist, C. (The Journal of Strength and Conditioning Research, 2020)
The aims of this study were to (a) examine changes in group and individual HR measures during a submaximal warm-up test, and (b) investigate the relationship between accumulated internal training loads and HR changes during an in-season phase among elite soccer players (n = 14). Before and after an in-season phase (24 days), exercise HR (HRex) and HR recovery (HRR) expressed either as the number of beats recovered (HRR60s) or as the mean HR (HRpost1) during 1 minute of recovery were analyzed. Heart rate measures were expressed as the % of maximal HR. Session rating of perceived exertion (sRPE) was computed for all training/match sessions. Group and individual HR changes were analyzed using magnitude-based inferences. Pearson correlation coefficients were also used to examine the relationships. Group analyses of HR changes revealed there were possibly to likely trivial changes in all HR measures. When analyzing individual data, no substantial change was observed for HRR60s%. However, substantial changes in HRex% and HRpost1% were observed for 4/14 and 5/14 players, respectively. The relationships between HRex% and HRpost1% were nearly perfect (r = 0.90, confidence limits [0.82-0.95]). The associations between changes in HRex% and HRpost1% were also nearly perfect (r = 0.92, 0.80-0.97). A very large inverse correlation was observed between HRex% and accumulated sRPE (r = -0.75, -0.44 to -0.90). This study highlights the value of conducting individual vs. group aerobic fitness monitoring. This study also showed the importance of how HRR is reported when aerobic fitness monitoring of elite soccer players.